O среднем значении функции S¯k(n) - Варбанец, П.Д.; Кирбат, С.А. (Український математичний журнал, 2011)
Побудовано асимптотичну формулу для середнього значення функцiї Sk(n), яка є дуальною до функцiї
Смарандача Sk(n). Отримано O- i Ω-оцiнки другого моменту залишкового члена. An asymptotic formula is constructed for a mean value of the function Sk(n) which is dual to the Smarandache
function Sk(n). O- and Ω-estimates for the second moment of the remainder term are obtained.